Toxicity Effect by Binahong (Anredera cordifolia) Leaf Extract in Histopathology and Liver Weight of Guinea Pigs (Cavia cobaya) - Dwi Wijayanti; Edy Kurnianto; Enny Tantini Setiatin (Buletin Peternakan, 2019)
The aim of this research was to determine the toxic effect of Anredera cordifolia leaf extract on the Cavia cobaya liver which was evaluated by the histopathological examination of liver tissue. The materials used were 8 female guinea pigs 2.5 months old that were divided into 4 groups by simple random sampling, each treatment was given to 2 female C. cobaya. Treatments given were 0, 10, 50 and 90 mg of A. cordifolia leaf extract/head, designated as T0, T1, T2 and T3, respectively. Materials were given treatment daily as long as 10 days prepartum. All of the guinea pigs were slaughtered at day 11, and the liver were taken to examined their histopathological changes. Each of the liver tissues were processed by paraffin block-embedded and hematoxylin eosin (HE) staining method. The results of this study indicate the presence of albuminosa degeneration or mild degeneration (DH +) from group control and hydropic degeneration or moderate degeneration (DH ++) in all treatment groups and the weight of C. cobaya liver which was given an extract of A. cordifolia 50 mg/head was not significantly different from the control but was significantly different from 10 and 90 mg/head. The conclusion was Binahong's (A. cordifolia) leaves extract up to the dosage 90 mg/head had no significantly toxicity effect on the liver of guinea pigs (C. cobaya).